Temporal stability of Glossina fuscipes fuscipes populations in Uganda - Echodu, Richard; Beadell, Jon S.; Okedi, Loyce M.; Hyseni, Chaz; Aksoy, Serap; Caccone, Adalgisa (Parasites & vectors, 2011)
Glossina fuscipes, a riverine species of tsetse, is the major vector of human African trypanosomiasis (HAT) in sub-Saharan Africa. Understanding the population dynamics, and specifically the temporal stability, of G. fuscipes will be important for informing vector control activities. We evaluated genetic changes over time in seven populations of the subspecies G. f. fuscipes distributed across southeastern Uganda, including a zone of contact between two historically isolated lineages. A total of 667 tsetse flies were genotyped at 16 microsatellite loci and at one mitochondrial locus. Results: Results of an AMOVA indicated that time of sampling did not explain a significant proportion of the variance in allele frequencies observed across all samples. Estimates of differentiation between samples from a single population ranged from approximately 0 to 0.019, using Jost’s DEST. Effective population size estimates using momentum-based and likelihood methods were generally large. We observed significant change in mitochondrial haplotype frequencies in just one population, located along the zone of contact. The change in haplotypes was not accompanied by changes in microsatellite frequencies, raising the possibility of asymmetric mating compatibility in this zone. Conclusion: Our results suggest that populations of G. f. fuscipes were stable over the 8-12 generations studied. Future studies should aim to reconcile these data with observed seasonal fluctuations in the apparent density of tsetse.
Keywords: Temporal stability; Glossina fuscipes fuscipes populations; Uganda